Credit Policy at the Discount Window - Whittlesey, C. R. (Quarterly Journal of Economics, 1959)
Misconceptions concerning discount practices, 207. — How limitation of discounting is effected, 210. — Interaction with the tradition against borrowing, 212. — Conclusion. 214.